Masonry Wall Numerical Simulation Using the Concrete Damage Plasticity Model - Suraj D. Bhosale; Atul K. Desai (New Approaches in Engineering Research Vol. 2, 2021)
The aim of this paper is to investigate the use of the FE (Finite Element) tool in analyzing masonry walls. Masonry is made up of highly nonlinear materials that have different properties depending on where they are used. Experimenting on a full-scale model of a masonry wall is challenging. Its impact is also undervalued in the construction of low-rise structures. As if the wall was properly confined and bonded to the beam and column. It improves the seismic efficiency of low-rise buildings. Energy is dissipated by cracking, much as it is in low-rise buildings. When a masonry wall is cast monolithically (like confined masonry) with the column, it increases the stiffness of the building and allows it to withstand additional load. The FE tool is used to perform a numerical nonlinear analysis of a wall panel in this research (ABAQUS). Using a Damage Plasticity Model for Concrete (CDP) and the findings are compared to previous studies by other researchers, with the conclusion that the results were satisfactory.